A RFID anti-collision algorithm based on multithread regressive-style binary system - Jin Di; Ma YanMin; Fan ZhiPeng; Fu Xiaolin (2012 International Conference on Measurement, Information and Control, 2012)
This paper aims at solving the conflicts among the problems of RFID. Based on the analysis of the original binary anti-collision algorithm, it puts forward a new algorithm to improve the identifying speed of RFID tag and to optimize the system performance. The algorithm is mainly inclusive of the backward technology, stack data structure and multithreading processing. With the RFID reader sending triad commands and the RFID tag's responding the collision bit' information, it aims to decrease the amount of data transmission; With applying the stack storing RFID to send commands, it aims to identify times of conflicts; With applying the multithreading notion to classify the labels, it aims to shorten processing time of conflicts. The analysis of experimental results shows that compared with original algorithm, this algorithm reduces the times of identifying conflicts and the amount of data transmission, which improves the system performance.